On the progenitor of the type Ia supernova remnant 0509-67.5 - Noam Soker (The Open Journal of Astrophysics)
Based on the iron and hydrogen similar elliptical morphologies of the type Ia supernova (SN Ia) remnant (SNR)~0509-67.5, I suggest that the ambient gas shaped the SN ejecta, that it is a remnant of an old planetary nebula, and that the explosion was spherical. Adding that there is no observed stellar survivor in this SNR, known to be an SN Ia,I conclude that the SN Ia scenarios that best account for the explosion of this SN inside a planetary nebula (SNIP) are the lonely white dwarf scenarios, i.e., the core-degenerate (CD) and the double degenerate (DD) with merger to explosion delay (MED) time, i.e., the DD-MED scenario. Other scenarios encounter challenges, but I cannot completely rule them out. If true, the suggestion of SNR~0509-67.5 being an SNIP implies that the fraction of SNIPs might be higher than the previously estimated 50 percent of all normal SNe Ia. In the frame of the CD and the DD-MED scenarios, I attribute the observed double-shell structure in calcium to Rayleigh-Taylor instability during the explosion process: the caps of the Rayleigh-Taylor instability mushrooms form the outer shell. Instabilities during the explosion process might form clumps of some elements moving much faster than their mean velocity, possibly explaining fast-moving intermediate-mass elements.